Report of the Working Group on Prunus: (Fourth meeting), Held at INRA, Bordeaux, France 30 November - 2 December 1992 - Frison, Emile A.; Tobutt, K.R.; International Board for Plant Genetic Resources; European Cooperative Programme for Plant Genetic Resources (1992)
Report of the Working Group on Prunus, fourth meeting, Held at INRA, Bordeaux, France 30 November - 2 December 1992